2021
DOI: 10.21203/rs.3.rs-922624/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single Cell Sequencing Analysis Identifies Genetics-Modulated ORMDL3+ Cholangiocytes Having Higher Metabolic Effects On Primary Biliary Cholangitis

Abstract: Background: Primary biliary cholangitis (PBC) is a classical autoimmune disease, which is highly influenced by genetic determinants. Many genome-wide association studies (GWAS) have reported that numerous genetic loci were significantly associated with PBC susceptibility. However, the effects of genetic determinants on liver cells and its immune microenvironment for PBC remain unclear. Results: We constructed a powerful computational framework to integrate GWAS summary statistics with scRNA-seq data to uncover… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Second, the identification of COVID-19-relevant cell types or subpopulations does not imply causality but may reflect indirect discovery of causal phenotype-cell associations, analogous to earlier studies [24,56]. Third, we removed the MHC region from all genomic analyses to reduce the influence of the complex genetic architecture and extensively high levels of LD, parallel to previous studies [8,24]. However, it should be noted that COVID-19-relevent genetic signals in this locus might be ignored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the identification of COVID-19-relevant cell types or subpopulations does not imply causality but may reflect indirect discovery of causal phenotype-cell associations, analogous to earlier studies [24,56]. Third, we removed the MHC region from all genomic analyses to reduce the influence of the complex genetic architecture and extensively high levels of LD, parallel to previous studies [8,24]. However, it should be noted that COVID-19-relevent genetic signals in this locus might be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…First, the power of the cell-type-level integration analysis is limited by the lack of scRNA-seq data and matched genetic information in each sample for discerning COVID-19-relevant cell types. To diminish the impact of this limitation, we adopted a powerful approach by incorporating a large-scale GWAS summary dataset and human organoids scRNA-seq data with a large amount of cells, as reference to previous studies [8,23,24,27,56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interrogation of PBC susceptibility-associated gene variants in an scRNA-seq dataset revealed the immune-modulatory role of ORMDL3 expression in cholangiocytes. 58 ORMDL3 + cholangiocytes were highly metabolically active and interacted with macrophages and monocytes via the vascular endothelial growth factor (VEGF) pathway. In PSC, scRNA-seq studies identified the expansion of a unique population of naive-like CD4 + T-cells with the potential to develop into Th17 cells.…”
Section: Microenvironmental Reprogramming In Chronic Liver Diseasementioning
confidence: 99%
“…For example, genome-wide association studies (GWAS) have clarified the role of the host genetic background in many disease states, like ulcerative colitis, PSC, PBC, and CLD. 58 100 101 102 103 In the future, a unique application of scRNA-seq in combination with such GWAS analyses could delineate the precise cellular source of such disease-associated gene variants. 104 105 While these combined analyses are still being refined, they have previously clarified the cellular origins for genetic alterations of interest in ulcerative colitis 105 and could be applied to autoimmune liver diseases.…”
Section: Future Perspectivesmentioning
confidence: 99%